A theory of the super soldier : the morality of capacity-increasing technologies in the military - Caron, Jean-François (Manchester Security, Conflict & Peace, 2018)
Super soldiers are about to become the new actors in the battlefields of tomorrow. Armed with science fiction-esque equipment and drugs, they are about to make comic book and Hollywood superheroes a reality.